Do players competing in the UEFA Champions League maintain running performance until the end of the match? Positional analysis between halves and 5-minute intervals - Kolodziejczyk, M.; Chmura, P.; Modric, T.; Versic, S.; Andrzejewski, M.; Chmura, J.; Sekulic, D.; Rokita, A.; Konefal, M. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: This investigation aimed to analyze differences in running performances amongst playing positions between the first and second halves of soccer matches and at 5-minute intervals during matches. METHODS: Data were collected from 179 soccer players during 20 UEFA Champions League (UCL) 2020/2021 group stage matches. Data were examined using the InStat Fitness semi-automatic video system. Eight variables were selected to quantify players` running performance (RP). Players were categorized based on positional groups: central defenders (CD), fullbacks (FB), central midfielders (CM), wide midfielders (WM), and forwards (FW). Univariate differences in RP were analyzed using ANOVA and the t-test for dependent samples and multivariate differences were identified using canonical discriminant analysis. RESULTS: The main findings were that all positions achieved significantly higher average speeds and walking distances in the first half of the match than in the second half. Furthermore, analysis of positions showed that CM covered more distance than CD in all 5-minute intervals. In addition, WM performed more high-intensity running than CD in all 5-minute intervals and FW performed more high-intensity running than all other playing positions. CONCLUSIONS: The findings from the present study should help coaches design training exercises that are specific to parts of a match. Moreover, the findings can help provide better understanding of match demands and individualization of training. Analysis of 5-minute intervals may also help coaches understand the stages of a match where player substitutions will be most effective.